Analytical assessment of restraint forces and crack widths in end-restrained building slabs. (1st December 2020) - Schlicke, Dirk; Tue, Nguyen Viet; Gomes, José; Sousa, Carlos; Azenha, Miguel
Highlights: Development of an analytical design tool for end-restrained building slabs. Prediction of crack width in end-restrained bending members. Transparent determination of restraint forces in jointless buildings. Role of restraint forces in bending members to achieve deformation compatibility. Abstract: This paper deals with the analytical assessment of restraint forces and crack widths in end-restrained building slabs. The analysis concentrates on the service limit state (SLS) and the challenge is hereby the appropriate consideration of the combined effect of axial restraint due to imposed deformations and bending cracking due to loading. As for the imposed deformations, the paper regards the drying shrinkage of concrete under indoor conditions, although any other temperature deformation or combination of shrinkage and temperature could be included accordingly. A deformation-based approach is presented, in which imposed deformations are made compatible with the released deformations of the slab due to opening of loading-induced bending cracks. The solution aims an appropriate inclusion of the most relevant effects while still providing a practicable and verifiable solution for the complex problem of assessing the restraint forces as well as the crack widths in end-restrained building slabs. The result of this approach is an analytical quantification of restraint forces to be transferred in the restraining members. In addition, the presented approach enables the determination of crack widths in the restrained conditions. An important asset of the analytical nature of this approach is the explicit correlation between individual system parameters, especially concrete properties and surrounding conditions, member dimensions and provided reinforcement, loading in the SLS and restraining condition. The paper includes the presentation of the general idea of a deformation-based assessment of end-restrained building slabs; the demonstration of this approach with an example from the literature; and the comparison of the analytical design solution with experimental results on the combined effect of bending and axial restraint in slab-like specimens.